Effect of acute kidney injury care bundle on kidney outcomes in cardiac patients receiving critical care: a systematic review and meta-analysis - Fatma Refaat Ahmed; Nabeel Al-Yateem; Seyed Aria Nejadghaderi; Rawia Gamil; Mohannad Eid AbuRuz (BMC Nephrology)
Abstract Background Cardiac surgery is a major contributor to acute kidney injury (AKI); approximately 22% of patients who undergo cardiac surgery develop AKI, and among them, 2% will require renal replacement therapy (RRT). AKI is also associated with heightened risks of mortality and morbidity, longer intensive care stays, and increased treatment costs. Due to the challenges of treating AKI, prevention through the use of care bundles is suggested as an effective approach. This review aimed to assess the impact of care bundles on kidney outcomes, mortality, and hospital stay for cardiac patients in critical care. Methods PubMed, Scopus, Web of Science, and EMBASE were searched up to November 2024. Inclusion criteria were studies on individuals with cardiac diseases receiving critical care, that used AKI care bundle as the intervention, and reported outcomes related to AKI, mortality, and other kidney-related events. We used the Cochrane Collaboration’s risk of bias tool 2 and the Newcastle-Ottawa scale for quality assessment. Pooled odds ratios (ORs) or risk ratios (RRs) with 95% confidence intervals (CIs) were calculated. Results Seven studies on total 5045 subjects, including five observational and two randomized controlled trials (RCTs) were included. The implementation of care bundles significantly reduced the incidence of all-stage AKI (OR: 0.78; 95%CI: 0.61–0.99) and moderate-severe AKI (OR: 0.56; 95%CI: 0.43–0.72). Also, the implementation of care bundle increased the incidence of persistent renal dysfunction after 30 days by 2.39 times. However, there were no significant changes in RRT, major adverse kidney events, or mortality between the groups. The mean quality assessment score for observational studies was 7.2 out of ten, while there were noted concerns in the risk of bias assessment of the RCTs. Conclusions The application of care bundles in patients, including those undergoing cardiac surgeries as well as non-cardiac critical illness, appears to be effective in reducing AKI, particularly in moderate and severe stages. However, given the inclusion of non-cardiac patients in some studies, the observed effect may not be solely attributable to cardiac surgery cases. Future large-scale RCTs focusing specifically on cardiac surgery patients are recommended to clarify the impact of care bundles within this subgroup. Registration ID in PROSPERO CRD42024498972.